Method for preparing iron-based SCR (Selective Catalytic Reduction) catalyst for denitration by utilizing pyrite cinder

By etching the pyrote slag, the etching dissolution solution and porous iron oxide mainly used as iron elements were separated, and a highly active iron-based SCR catalyst was prepared, which solved the technical obstacles to the separation and utilization of complex components of pyrote slag, and achieved efficient resource utilization and environmental protection.

CN119657176APending Publication Date: 2025-03-21INST OF COAL CHEM CHINESE ACAD OF SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510008527.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The technical barriers to the separation and utilization of complex components of pyrote ore slag lead to low comprehensive utilization rate and long-term stacking lead to soil and water pollution.

Method used

By etching the pyrote slag, the etching dissolution solution and porous iron oxide mainly used as active components and support for the preparation of the catalyst. After calcination and activation, the iron-based SCR catalyst was prepared.

Benefits of technology

The full component reuse of pyrote ore slag has been realized, the activity and temperature application window of catalysts have been improved, and resource waste and environmental pollution have been reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119657176A_ABST
    Figure CN119657176A_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing an iron-based SCR (Selective Catalytic Reduction) catalyst for denitration by utilizing pyrite cinder, and belongs to the technical field of industrial solid waste reutilization. The method comprises the following steps: soaking and etching the pyrite cinder in an etching solution, carrying out solid-liquid separation, and treating the obtained solid to obtain a carrier main material; mixing the carrier main material with the auxiliary material, molding, aging and airing, drying, and carrying out first calcination to obtain a catalyst carrier; and soaking a catalyst carrier in the separated liquid, taking out, drying, carrying out secondary calcination to obtain a catalyst semi-finished product, and finally activating to obtain the catalyst. According to the iron-based SCR catalyst carrier and the preparation method thereof, pyrite cinder is subjected to etching treatment, a solid material obtained after etching treatment is used for preparing the catalyst carrier, etching dissolution liquid of an iron element and other microelements is used as an active component for preparing a catalyst, and the iron-based SCR catalyst carrier is obtained after loading, calcination and activation. Therefore, all-component development and utilization of the pyrite cinder waste are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of industrial solid waste recycling, and in particular relates to a method for preparing an iron-based SCR catalyst for denitration by utilizing pyrite cinder. Background Art

[0002] Pyrite cinder is a kind of iron-rich solid waste discharged after high-temperature oxidation roasting in a fluidized bed using pyrite as raw material in the production of sulfuric acid. The cinder can be used for building materials, preparation of iron salts, recovery of non-ferrous metals, etc., but due to its high silicon and sulfur content, the comprehensive utilization rate is only 30%. Most of the cinder is landfilled, which not only occupies a large amount of land, but also causes serious waste of resources. In addition, the harmful components such as sulfur in the long-term stacked pyrite cinder will cause serious soil and water pollution through weathering, rain and seepage. It is urgent to develop new utilization channels to achieve high-value utilization of pyrite cinder.

[0003] Iron-based catalysts are cheap and readily available, and are widely used in many fields. Patent CN114471564B discloses a high-load medium-low temperature iron-based denitrification catalyst and a preparation method thereof, wherein the iron salt used can be directly extracted from pyrite cinders. In addition, it is worth noting that trace elements such as gold, silver, and nickel in pyrite cinders are also very ideal SCR denitrification active components, which can be extracted together with iron elements and used as catalyst active components. Therefore, how to overcome the technical barriers to the separation and utilization of the complex components of pyrite cinders, realize the reuse of all components of pyrite cinders, and then prepare iron-based catalysts, needs to be developed and explored.

[0004] In view of this, this application is hereby filed. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing an iron-based SCR catalyst for denitrification using pyrite cinders, wherein the pyrite cinders are etched and the etched solid material is used to prepare a catalyst carrier. At the same time, the etching solution mainly containing iron and other trace elements is used as an active component for preparing the catalyst, and the iron-based SCR catalyst carrier is obtained after loading, calcination and activation, thereby realizing the development and utilization of all components of the pyrite cinder waste.

[0006] In order to achieve the above objectives, the present invention particularly adopts the following technical solutions:

[0007] The present invention provides a method for preparing an iron-based SCR catalyst for denitration using pyrite cinder, comprising the following steps:

[0008] S1: soaking the pyrite slag in an etching solution, etching it, and then separating the solid from the liquid. The solid obtained by separation is treated to obtain a porous iron oxide with a high specific surface area, which is used as a main material of the catalyst carrier.

[0009] Furthermore, the etching solution includes a sulfur-containing solution.

[0010] Preferably, the method for preparing the etching solution comprises: using an aqueous solution of hydrogen peroxide to absorb and oxidize the activated tail gas of the subsequent step S4, to obtain the etching solution.

[0011] Further, the mass fraction of the aqueous solution of hydrogen peroxide is 5-60%; preferably, the mass fraction of the aqueous solution of hydrogen peroxide is 15-30%.

[0012] Further preferably, the aqueous solution of hydrogen peroxide may also include alkyl alcohol amine or fluorinated alkyl alcohol amine, which can improve the absorption efficiency of the collected tail gas and also reduce the viscosity of the etching solution, thereby facilitating subsequent solid-liquid separation.

[0013] Furthermore, the mass fraction of the alkyl alcohol amine or fluorinated alkyl alcohol amine in the aqueous solution of hydrogen peroxide is 0.5-2.5%.

[0014] The amount ratio of the etching solution to the pyrite slag is such that the H + Fe dissolved by etching 3+ The molar ratio of (Fe2O3 in pyrite slag) is 3-6:1.

[0015] The reaction equation is: Fe2O3+6H + =2Fe 3+ +3H2O.

[0016] That is, the Fe dissolved by etching can be calculated based on the total amount of pyrite slag, the content of iron element and the designed dissolution rate of iron element. 3+ The molar amount of H + The molar amount of H + The concentration of the etching solution is calculated.

[0017] Furthermore, the temperature of the etching solution is controlled to be 50-110° C., and the etching time is 2-48 hours. Preferably, the temperature of the etching solution is controlled to be 70-90° C., and the etching time is 24-36 hours.

[0018] Furthermore, the dissolution rate of the iron element in the liquid obtained after the solid-liquid separation is controlled to be 15-45%. Preferably, the dissolution rate of the iron element in the liquid obtained after the solid-liquid separation is controlled to be 20-35%.

[0019] Preferably, the obtained pyrite cinder etching product can be crushed to a mesh size of ≤100 mesh.

[0020] Step S1 utilizes the structure and phase differences of pyrite slag to partially etch and dissolve the iron oxides through a unique etching solution that can be circulated from this process, thereby obtaining a pyrite slag having a sintering effect.

[0021] The etched product has a porous structure. The obtained product is mainly iron oxide, containing a small amount of silicon and aluminum oxide, which is an ideal raw material for preparing the carrier component used in the denitrification catalyst. The etched solution is mainly iron ions, and also contains a small amount of gold, silver, nickel and other elements, which can be used as catalyst active components.

[0022] S2: Mixing the carrier main material and auxiliary materials, forming, aging and air-drying, and drying, and obtaining a catalyst carrier after a first calcination.

[0023] Preferably, when the carrier main material is mixed with the auxiliary material, auxiliary agents such as hydrogen peroxide, pH regulator, lubricant, pore-forming agent, etc. may also be added.

[0024] Optionally, the auxiliary material comprises pyrite powder.

[0025] Preferably, the pyrite powder is crushed to a mesh size of ≤100 mesh.

[0026] Preferably, the mass ratio of the pyrite powder to the carrier main material is 1-3:10.

[0027] Preferably, adding 0.5-1% by mass of hydroxyethyl cellulose to the pyrite powder can delay its solidification.

[0028] Preferably, the auxiliary materials also include active titanium dioxide and / or glass fiber. Active titanium dioxide is used as an auxiliary material for catalyst carriers to improve the plasticity of the molding mud and the pore structure of the obtained catalyst, and its addition amount is 5-30% of the weight of the carrier main material; the purpose of adding glass fiber is to improve the structural strength of the catalyst, and its addition amount is 1-6% of the weight of the carrier main material.

[0029] Furthermore, the amount of hydrogen peroxide used satisfies a molar ratio of H2O2 to FeS2 in the added pyrite powder of 15-17:2.

[0030] Reaction equation: 2FeS2+15H2O2=2Fe 3+ +4SO4 2- +14H2O+2H + .

[0031] Furthermore, the pH adjuster comprises one or more of ammonium carbonate, ammonia water or liquid ammonia, in order to neutralize the acidity of the above reaction.

[0032] Furthermore, the lubricant includes phthalate or epoxy oleate, and the added amount of the lubricant is 0.1-0.4% of the mass of the carrier main material.

[0033] Furthermore, the pore-forming agent includes biomass fiber powder, and the amount of the pore-forming agent added is 0.5-4% of the mass of the main material of the carrier.

[0034] Furthermore, the aging, air-drying, drying and first calcination process includes: controlling the relative humidity at 85-95% for aging at 45-60°C for 24-96h, drying at 105-120°C for 3-8h, calcining at 450-520°C for 1-6h, and a heating rate of 1-10°C / min.

[0035] Preferably, the aging, air-drying, drying and first calcination process includes: aging at 50°C for 48h at a relative humidity of 90%, drying at 110°C for 4-6h, calcining at 470-495°C for 3h, and a heating rate of 2-5°C / min.

[0036] In the catalyst preparation process of the present application, sulfur elements circulate, change, and are recycled in different chemical forms, playing the role of an iron atom carrier. The auxiliary material pyrite powder used in step S2 can provide the necessary sulfur elements for the catalyst preparation process on the one hand, and on the other hand, its easy consolidation characteristics can be used to improve the strength of the formed blanks in the catalyst preparation process.

[0037] S3: soaking the catalyst carrier in the liquid separated in step S1, taking it out and drying it, and obtaining a catalyst semi-finished product after a second calcination.

[0038] Preferably, the liquid obtained after the solid-liquid separation is diluted with deionized water to a mass fraction of iron element of 8-15%.

[0039] Preferably, a pH adjuster is used to adjust the pH value of the liquid obtained after the solid-liquid separation to 1-2.5; more preferably, the pH adjuster comprises one or more of ammonium carbonate, ammonia water or liquid ammonia.

[0040] Furthermore, during the soaking, the temperature of the soaking liquid is controlled to be 55-70° C., and the soaking time is 1-3 hours.

[0041] Furthermore, the drying and secondary calcination process includes: drying at 105-150°C for 3-8h, calcining at 450-520°C for 1-6h, and a heating rate of 1-10°C / min.

[0042] Preferably, the drying and secondary calcination process includes: drying at 110-120°C for 4-6 hours, calcining at 470-495°C for 3 hours, and a heating rate of 2-5°C / min.

[0043] Preferably, step S3 may be repeated to increase the loading amount of the catalyst active components.

[0044] S4: Activate the semi-finished catalyst to obtain the catalyst. During the process, the sulfur-containing components in the activated tail gas are collected and cooled, absorbed, oxidized, and then used as the etching solution for preparing step S1.

[0045] Further, the activation includes a first activation and a second activation.

[0046] Preferably, the first activation is activation at 150-180° C. for 12-24 h; and the second activation is activation at 420-460° C. for 2-6 h.

[0047] Furthermore, the first activation atmosphere includes the tail gas of the first calcination and / or the tail gas of the second calcination. In the first activation, at a relatively low temperature, the sulfur-containing gas in the tail gas of the calcination adheres to the catalyst surface in the form of an oxygen-containing acid, which can induce atomic migration, diffusion and rearrangement of active components on the catalyst surface, thereby regulating the exposed crystal surface structure.

[0048] Furthermore, the second activation atmosphere includes air or a mixed atmosphere containing air; preferably, the second activation atmosphere includes a mixed gas of air and 0.05-0.2% by mass of ammonia. During the second activation, the sulfur element remaining on the catalyst surface is decomposed and leaves the catalyst surface.

[0049] After the above activation treatment, the denitration catalytic activity is greatly improved compared with the semi-finished catalyst, and the K value is increased by more than 50%.

[0050] Compared with the prior art, the present invention has the following characteristics and advantages:

[0051] (1) The pyrite slag is etched, and the etching solution mainly composed of iron elements is used as an active component for preparing a catalyst, and the porous iron oxide after etching is used to prepare a catalyst carrier. After impregnation, calcination and activation, an iron-based SCR catalyst is obtained.

[0052] (2) The retention and reuse of trace associated elements such as gold, silver, and nickel in pyrite slag are achieved, which are used as supplementary active components of the denitrification catalyst, thereby improving the temperature application window of the catalyst.

[0053] (3) Cleverly utilize the physical and chemical properties of sulfur to allow it to act as a carrier of iron atoms and be recycled, thereby achieving the migration and transformation of iron atoms, orderly arrangement, and high activity of the catalyst.

[0054] (4) It has achieved the all-round development and utilization of pyrite slag waste. The process is green and environmentally friendly and no waste is generated. It has high economic and social value. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0056] Figure 1 The present invention is a process flow chart for preparing an iron-based SCR catalyst for denitrification using pyrite cinder. DETAILED DESCRIPTION

[0057] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0058] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0059] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range.

[0060] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0061] The ratios not given in the examples are all arbitrary ratios, and the ratio units not given are all mass ratios. The raw materials are all conventional commercial products. Among them, the pyrite slag uses a pyrite sulfuric acid production device of Guizhou Phosphate (Group) Co., Ltd., and the iron content is 47.3%. The iron content of pyrite slag from other manufacturers on the market is different, but it does not affect the understanding of the implementation of the present invention, and can be implemented according to the ratio and process range of the present invention.

[0062] The denitration activity of the catalysts obtained in the examples and comparative examples was tested under the conditions of simulated flue gas in a fixed bed reactor.

[0063] Test conditions: reaction temperature 270-390℃, catalyst loading volume 4L, flue gas flow rate 15Nm 3 / h, NO concentration 200ppm, ammonia nitrogen molar ratio = 1.0, SO2 concentration 300ppm, oxygen concentration 6.0%, water content 10.0%, nitrogen as the balance gas.

[0064] Example 1

[0065] A method for preparing an iron-based SCR catalyst for denitration using pyrite slag, combined with Figure 1 As shown, the following steps are included:

[0066] (1) The pyrite slag is immersed in an etching solution (25% sulfuric acid is used for the initial etching, and the etching solution prepared by absorbing and oxidizing the activated tail gas in step (8) with a 30% hydrogen peroxide aqueous solution, and 1.5% alkyl alcohol amine is added to the hydrogen peroxide aqueous solution) for etching treatment, and the liquid-to-solid ratio satisfies the H + Fe dissolved by etching 3 + The molar ratio of (Fe2O3 in pyrite slag) is 4.5:1, the immersion etching temperature is 85°C, the immersion etching time is 24h, and the dissolution rate of the iron element is controlled to be 30%.

[0067] (2) Separate the etched pyrite cinder from the liquid, wash, dry, crush, and grind to a mesh size of ≤200 to obtain porous iron oxide, which is used as the main carrier material for preparing the catalyst. Dilute the separated solution with deionized water to a mass fraction of 12% iron; adjust the pH value of the solution to 1.3 with ammonium carbonate; and maintain the temperature of the solution at 60°C. Thus, a pyrite cinder active component liquid mainly composed of iron ions and also containing trace elements such as gold, silver, and nickel is obtained, which is used as the active component for preparing the catalyst.

[0068] (3) The pyrite powder is crushed to ≤200 meshes, and 0.7% of hydroxyethyl cellulose is added to the powder to obtain the first auxiliary material, which is mixed with the carrier main material porous iron oxide at a mass ratio of 2:10, and then active titanium dioxide and glass fiber are mixed, wherein the amount of active titanium dioxide added is 8% of the mass of the carrier main material, and the amount of glass fiber added is 2% of the mass of the carrier main material. Then water is added and stirred, and hydrogen peroxide, ammonia water, phthalate and biomass fiber powder are added to knead the mud to obtain a molded blank. Among them, the amount of hydrogen peroxide added is 17:2 according to the molar ratio of H2O2 to FeS2 in the added pyrite powder, the amount of ammonia water added is until the system is neutral, the amount of phthalate added is 0.2%, and the amount of biomass fiber powder added is 1%.

[0069] (4) The formed blank was aged at 55°C for 48 hours, and the relative humidity was controlled at 90%; the drying time was 110°C for 5 hours, and the calcination time was 480°C for 4 hours, and the heating rate was 3°C / min. After calcination, the catalyst carrier was obtained, and the calcination tail gas was discharged without treatment and introduced into the subsequent process to improve the catalyst activity.

[0070] (5) Soak the catalyst carrier obtained in step (4) in the solution obtained in step (2) for 2 hours at a soaking temperature of 60°C; take out and drain, then dry at 125°C for 6 hours; then calcine at 480°C for 4 hours at a heating rate of 3°C / min. After calcination, a semi-finished catalyst is obtained, and the calcination tail gas is discharged without treatment and introduced into the subsequent process to improve the catalyst activity.

[0071] (6) Repeat step (5) to increase the loading amount of the active component.

[0072] (7) The calcined tail gas from step (4), step (5) and step (6) was introduced to activate the semi-finished catalyst obtained in step (6), and the activation conditions were as follows: activation at 165° C. for 18 h; then the temperature was raised to 440° C. and maintained in a mixed atmosphere of air and 0.1% ammonia for 4 h, and a finished iron-based SCR catalyst was obtained. The activity test results are shown in Table 1.

[0073] (8) The activated tail gas from step (7) is collected, cooled, and then absorbed and oxidized with a 30% hydrogen peroxide aqueous solution (the hydrogen peroxide aqueous solution contains 1.5% by mass of alkyl alcohol amine) to obtain the etching solution used in step (1).

[0074] Example 2

[0075] A method for preparing an iron-based SCR catalyst for denitration using pyrite slag, combined with Figure 1 As shown, the following steps are included:

[0076] (1) The pyrite slag is immersed in an etching solution (25% sulfuric acid is used for the initial etching, and the etching solution prepared by absorbing and oxidizing the activated tail gas in step (8) with a 30% hydrogen peroxide aqueous solution, and 1% alkyl alcohol amine is added to the hydrogen peroxide aqueous solution) for etching treatment, and the liquid-to-solid ratio satisfies the H + Fe dissolved by etching 3+ The molar ratio of (Fe2O3 in pyrite slag) is 6:1, the immersion etching temperature is 100°C, the immersion etching time is 8h, and the dissolution rate of the iron element is controlled to be 35%.

[0077] (2) Separate the etched pyrite cinder from the liquid, wash, dry, crush, and grind to a mesh size of ≤300 to obtain porous iron oxide, which is used as the main carrier material for preparing the catalyst. Dilute the separated solution with deionized water to a mass fraction of iron element of 15%; adjust the pH value of the solution to 1 with ammonia water; and maintain the temperature of the solution at 65°C. Thus, a pyrite cinder active component liquid mainly composed of iron ions and also containing trace elements such as gold, silver, and nickel is obtained, which is used as the active component for preparing the catalyst.

[0078] (3) The pyrite powder is crushed to ≤300 mesh, and 0.9% of hydroxyethyl cellulose is added to the powder to obtain the first auxiliary material, which is mixed with the carrier main material porous iron oxide at a mass ratio of 2.5:10, and then active titanium dioxide and glass fiber are mixed, wherein the amount of active titanium dioxide added is 10% of the mass of the carrier main material, and the amount of glass fiber added is 4% of the mass of the carrier main material. Then water is added and stirred, and hydrogen peroxide, ammonia water, phthalate and biomass fiber powder are added to knead the mud to obtain a molded blank. Among them, the amount of hydrogen peroxide added is 16:2 according to the molar ratio of H2O2 to FeS2 in the added pyrite powder, the amount of ammonia water added is until the system is neutral, the amount of phthalate added is 0.1%, and the amount of biomass fiber powder added is 1.5%.

[0079] (4) The formed blank was aged at 55°C for 72 hours, and the relative humidity was controlled at 92%; the drying time was 115°C for 7 hours, and the calcination time was 495°C for 4 hours, and the heating rate was 5°C / min. After calcination, the catalyst carrier was obtained, and the calcination tail gas was discharged without treatment and introduced into the subsequent process to improve the catalyst activity.

[0080] (5) Soak the catalyst carrier obtained in step (4) in the dissolution solution obtained in step (2) for 2.5 hours at a soaking temperature of 65°C; take out and drain, dry at 135°C for 7 hours; then calcine at 495°C for 3 hours at a heating rate of 5°C / min. After calcination, a semi-finished catalyst is obtained, and the calcination tail gas is discharged without treatment and introduced into the subsequent process to improve the catalyst activity.

[0081] (6) Repeat step (5) to increase the loading amount of the active component.

[0082] (7) The calcined tail gas from step (4), step (5) and step (6) was introduced to activate the semi-finished catalyst obtained in step (6), and the activation conditions were as follows: activation at 180° C. for 24 h; then the temperature was raised to 450° C. and maintained in a mixed atmosphere of air and 0.15% ammonia for 4 h, and a finished iron-based SCR catalyst was obtained. The activity test results are shown in Table 1.

[0083] (8) The activated tail gas from step (7) is collected, cooled, and then absorbed and oxidized with a 30% hydrogen peroxide aqueous solution (the hydrogen peroxide aqueous solution contains 1% by mass of alkyl alcohol amine) to obtain the etching solution used in step (1).

[0084] Example 3

[0085] A method for preparing an iron-based SCR catalyst for denitration using pyrite slag, combined with Figure 1 As shown, the following steps are included:

[0086] (1) The pyrite slag is immersed in an etching solution (30% sulfuric acid is used for the initial etching, and the etching solution prepared by absorbing and oxidizing the activated tail gas in step (8) with 18% hydrogen peroxide aqueous solution, and 0.5% alkyl alcohol amine is added to the hydrogen peroxide aqueous solution) for etching treatment, and the liquid-to-solid ratio satisfies the H in the etching solution. + Fe dissolved by etching 3 + The molar ratio of (Fe2O3 in pyrite slag) is 3:1, the immersion etching temperature is 50°C, the immersion etching time is 48h, and the dissolution rate of the iron element is controlled to be 15%.

[0087] (2) Separate the etched pyrite cinder from the liquid, wash, dry, crush, and grind to a mesh size of ≤100 to obtain porous iron oxide, which is used as the main carrier material for preparing the catalyst. Dilute the separated solution with deionized water to a mass fraction of 15% iron; adjust the pH value of the solution to 1.1 with liquid ammonia; and maintain the temperature of the solution at 58°C. Thus, a pyrite cinder active component liquid mainly composed of iron ions and also containing trace elements such as gold, silver, and nickel is obtained, which is used as the active component for preparing the catalyst.

[0088] (3) The pyrite powder is crushed to ≤100 mesh, and 0.6% of hydroxyethyl cellulose is added to the powder to obtain the first auxiliary material, which is mixed with the carrier main material porous iron oxide at a mass ratio of 1.5:10, and then active titanium dioxide and glass fiber are mixed, wherein the amount of active titanium dioxide added is 15% of the mass of the carrier main material, and the amount of glass fiber added is 1% of the mass of the carrier main material. Then water is added and stirred, and hydrogen peroxide, ammonia water, phthalate and biomass fiber powder are added, and the clay is kneaded to obtain a molded blank. Among them, the amount of hydrogen peroxide added is 15:2 according to the molar ratio of H2O2 to FeS2 in the added pyrite powder, the amount of ammonia water added is until the system is neutral, the amount of phthalate added is 0.4%, and the amount of biomass fiber powder added is 3%.

[0089] (4) The formed blank was aged at 48°C for 30 hours, and the relative humidity was controlled at 88%; the drying time was 108°C for 4 hours, and the calcination time was 470°C for 5 hours, and the heating rate was 2°C / min. After calcination, the catalyst carrier was obtained, and the calcination tail gas was discharged without treatment and introduced into the subsequent process to improve the catalyst activity.

[0090] (5) Soak the catalyst carrier obtained in step (4) in the solution obtained in step (2) for 1.5 hours at a soaking temperature of 58°C; take out and drain, dry at 110°C for 4 hours; then calcine at 475°C for 5 hours at a heating rate of 2°C / min. After calcination, a semi-finished catalyst is obtained, and the calcination tail gas is discharged without treatment and introduced into the subsequent process to improve the catalyst activity.

[0091] (6) Repeat step (5) to increase the loading amount of the active component.

[0092] (7) The calcined tail gas from step (4), step (5) and step (6) was introduced to activate the semi-finished catalyst obtained in step (6), and the activation conditions were as follows: activation at 150° C. for 12 h; then the temperature was raised to 430° C. and maintained in a mixed atmosphere of air and 0.08% ammonia for 4 h, and a finished iron-based SCR catalyst was obtained. The activity test results are shown in Table 1.

[0093] (8) The activated tail gas from step (7) is collected, cooled, and then absorbed and oxidized with a 18% hydrogen peroxide aqueous solution (the hydrogen peroxide aqueous solution contains 0.5% by mass of alkyl alcohol amine) to obtain the etching solution used in step (1).

[0094] Example 4

[0095] A method for preparing an iron-based SCR catalyst for denitration using pyrite slag, combined with Figure 1 As shown, the following steps are included:

[0096] (1) The pyrite slag is immersed in an etching solution (35% sulfuric acid is used for the initial etching, and the etching solution prepared by absorbing and oxidizing the activated tail gas in step (8) with a 5% hydrogen peroxide aqueous solution, and 2.5% alkyl alcohol amine is added to the hydrogen peroxide aqueous solution) for etching treatment, and the liquid-to-solid ratio is based on the H + Fe dissolved by etching 3+ The molar ratio of (Fe2O3 in pyrite slag) is 4:1, the immersion etching temperature is 80°C, the immersion etching time is 36h, and the dissolution rate of the iron element is controlled to be 25%.

[0097] (2) Separate the etched pyrite cinder from the liquid, wash, dry, crush, and grind to a mesh size of ≤200 to obtain porous iron oxide, which is used as the main carrier material for preparing the catalyst. Dilute the separated solution with deionized water to a mass fraction of 8% iron; adjust the pH value of the solution to 1 with ammonia water; and maintain the temperature of the solution at 55°C. Thus, a pyrite cinder active component liquid mainly composed of iron ions and also containing trace elements such as gold, silver, and nickel is obtained, which is used as the active component for preparing the catalyst.

[0098] (3) The pyrite powder is crushed to ≤100 mesh, and 0.5% of hydroxyethyl cellulose is added to the powder to obtain the first auxiliary material, which is mixed with the carrier main material porous iron oxide at a mass ratio of 1:10, and then active titanium dioxide and glass fiber are mixed, wherein the amount of active titanium dioxide added is 20% of the mass of the carrier main material, and the amount of glass fiber added is 6% of the mass of the carrier main material. Then water is added and stirred, and hydrogen peroxide, ammonia water, phthalate and biomass fiber powder are added, and the clay is kneaded to obtain a molded blank. Among them, the amount of hydrogen peroxide added is 17:2 according to the molar ratio of H2O2 to FeS2 in the added pyrite powder, the amount of ammonia water added is until the system is neutral, the amount of phthalate added is 0.2%, and the amount of biomass fiber powder added is 4%.

[0099] (4) The formed blank was aged at 45°C for 96 hours, with the relative humidity controlled at 85%; dried at 105°C for 8 hours, and calcined at 450°C for 6 hours, with a heating rate of 1°C / min. After calcination, the catalyst carrier was obtained, and the calcination tail gas was discharged without treatment and introduced into the subsequent process to improve the catalyst activity.

[0100] (5) Soak the catalyst carrier obtained in step (4) in the solution obtained in step (2) for 2.5 hours at a soaking temperature of 55°C; take out and drain, dry at 105°C for 8 hours; then calcine at 450°C for 6 hours at a heating rate of 1°C / min. After calcination, a semi-finished catalyst is obtained, and the calcination tail gas is discharged without treatment and introduced into the subsequent process to improve the catalyst activity.

[0101] (6) Repeat step (5) to increase the loading amount of the active component.

[0102] (7) The calcined tail gas from step (4), step (5) and step (6) was introduced to activate the semi-finished catalyst obtained in step (6), and the activation conditions were as follows: activation at 120° C. for 48 h; then the temperature was raised to 420° C. and maintained in a mixed atmosphere of air and 0.2% ammonia for 6 h, and a finished iron-based SCR catalyst was obtained. The activity test results are shown in Table 1.

[0103] (8) The activated tail gas from step (7) is collected, cooled, and then absorbed and oxidized with a 5% hydrogen peroxide aqueous solution (the hydrogen peroxide aqueous solution contains 2.5% by mass of alkyl alcohol amine) to obtain the etching solution used in step (1).

[0104] Example 5

[0105] A method for preparing an iron-based SCR catalyst for denitration using pyrite slag, combined with Figure 1 As shown, the following steps are included:

[0106] (1) The pyrite slag is immersed in an etching solution (45% sulfuric acid is used for the initial etching, and the etching solution prepared by absorbing and oxidizing the activated tail gas in step (8) with a 60% hydrogen peroxide aqueous solution, and 2% by mass of alkyl alcohol amine is added to the hydrogen peroxide aqueous solution) for etching treatment, and the liquid-to-solid ratio satisfies the H + Fe dissolved by etching 3+ The molar ratio of (Fe2O3 in pyrite slag) is 5:1, the immersion etching temperature is 110°C, the immersion etching time is 2h, and the dissolution rate of the iron element is controlled to be 45%.

[0107] (2) Separate the etched pyrite cinder from the liquid, wash, dry, crush, and grind to a mesh size of ≤300 to obtain porous iron oxide, which is used as the main carrier material for preparing the catalyst. Dilute the separated solution with deionized water to a mass fraction of iron element of 15%; adjust the pH value of the solution to 2.5 with ammonia water; and maintain the temperature of the solution at 70°C. Thus, a pyrite cinder active component liquid mainly composed of iron ions and also containing trace elements such as gold, silver, and nickel is obtained, which is used as the active component for preparing the catalyst.

[0108] (3) The pyrite powder is crushed to ≤100 mesh, and 1% of hydroxyethyl cellulose is added to the powder to obtain the first auxiliary material, which is mixed with the carrier main material porous iron oxide at a mass ratio of 3:10, and then active titanium dioxide and glass fiber are mixed, wherein the amount of active titanium dioxide added is 5% of the mass of the carrier main material, and the amount of glass fiber added is 2% of the mass of the carrier main material. Then water is added and stirred, and hydrogen peroxide, ammonia water, phthalate and biomass fiber powder are added to knead the mud to obtain a molded blank. Among them, the amount of hydrogen peroxide added is 17:2 according to the molar ratio of H2O2 to FeS2 in the added pyrite powder, the amount of ammonia water added is until the system is neutral, the amount of phthalate added is 0.2%, and the amount of biomass fiber powder added is 0.5%.

[0109] (4) The formed blank was aged at 60°C for 24 hours, and the relative humidity was controlled at 95%; the drying time was 120°C for 3 hours, and the calcination time was 520°C for 1 hour, and the heating rate was 10°C / min. After calcination, the catalyst carrier was obtained, and the calcination tail gas was discharged without treatment and introduced into the subsequent process to improve the catalyst activity.

[0110] (5) Soak the catalyst carrier obtained in step (4) in the solution obtained in step (2) for 3 hours at a soaking temperature of 70°C; take out and drain, then dry at 150°C for 3 hours; then calcine at 520°C for 1 hour at a heating rate of 10°C / min. After calcination, a semi-finished catalyst is obtained, and the calcination tail gas is discharged without treatment and introduced into the subsequent process to improve the catalyst activity.

[0111] (6) Repeat step (5) to increase the loading amount of the active component.

[0112] (7) The calcined tail gas from step (4), step (5) and step (6) was introduced to activate the semi-finished catalyst obtained in step (6), and the activation conditions were as follows: activation at 200° C. for 2 h; then the temperature was raised to 460° C. and maintained in a mixed atmosphere of air and 0.2% ammonia for 2 h, and a finished iron-based SCR catalyst was obtained. The activity test results are shown in Table 1.

[0113] (8) The activated tail gas from step (7) is collected, cooled, and then absorbed and oxidized with a 60% hydrogen peroxide aqueous solution (the hydrogen peroxide aqueous solution contains 2% by mass of alkyl alcohol amine) to obtain the etching solution used in step (1).

[0114] Comparative Example 1

[0115] The difference compared with Example 1 is that the temperature of the dissolving solution in step (2) is 25°C, that is, the immersion temperature in step (5) is 25°C.

[0116] Comparative Example 2

[0117] The difference compared with Example 1 is that the first activation in step (7) is not performed.

[0118] Comparative Example 3

[0119] The difference compared with Example 1 is that the first activation and the second activation of step (7) are not performed.

[0120] Comparative Example 4

[0121] The difference compared with Example 1 is that in steps (1) and (8), no alkyl alcoholamine is added to the aqueous solution of hydrogen peroxide.

[0122] Table 1 Catalyst performance of Examples 1-5 and Comparative Examples 1-4

[0123]

[0124]

[0125] It can be seen from Table 1 that the iron-based SCR catalyst for denitrification prepared from pyrite cinder of the present invention has good catalytic activity and temperature applicable window.

[0126] The temperature of the dissolving solution in Comparative Example 1 during immersion was 25°C, which had a significant effect on the catalytic denitration rate, especially in the medium and low temperature range. It can be seen that keeping the dissolving solution at a certain temperature during immersion in the present invention can significantly improve the performance of the obtained catalyst.

[0127] Compared with the results of Example 1, the performance of the catalysts obtained without activation or without the first activation in Comparative Examples 2 and 3 is greatly reduced, especially the first activation has a greater impact.

[0128] In Comparative Example 4, no alkyl alcohol amine was added. The results showed that the absorption rate of activated tail gas was significantly reduced, which led to a decrease in the performance of the final catalyst.

[0129] Please note that the technical features of the above embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. The above embodiments only express several implementation methods of the present application, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several variations and improvements can be made, which all belong to the scope of protection of the present application. Therefore, the scope of protection of the patent in this application shall be based on the attached claims.

Claims

1. A method for preparing an iron-based SCR catalyst for denitrification using pyrite slag, characterized in that: The steps include: S1: soaking the pyrite slag in an etching solution to perform solid-liquid separation, and treating the solid obtained by separation to obtain a carrier main material; S2: mixing the carrier main material and auxiliary materials, forming, aging, air-drying, and drying, and obtaining a catalyst carrier after a first calcination; S3: soaking the catalyst carrier in the liquid separated in step S1, taking it out and drying it, and obtaining a catalyst semi-finished product after a second calcination; S4: activating the semi-finished catalyst to obtain the catalyst.

2. The method according to claim 1, characterized in that In step S1, the etching solution includes a sulfur-containing solution; Preferably, the method for preparing the etching solution comprises: absorbing and oxidizing the activated tail gas of the subsequent step S4 with an aqueous solution of hydrogen peroxide, to obtain; Preferably, the mass fraction of the aqueous solution of hydrogen peroxide is 5-60%.

3. The method according to claim 2, characterized in that In step S1, the aqueous solution of hydrogen peroxide also includes alkyl alcohol amine or fluorinated alkyl alcohol amine; Preferably, the mass fraction of the alkyl alcohol amine or fluorinated alkyl alcohol amine in the aqueous solution of hydrogen peroxide is 0.5-2.5%.

4. The method according to claim 1, characterized in that: In step S1, the amount ratio of the etching solution to the pyrite slag is such that the H + Fe dissolved by etching 3+ The molar ratio is 3-6:1; and / or, controlling the temperature of the etching solution to 50-110° C.; And / or, the dissolution rate of iron in the liquid obtained after the solid-liquid separation is controlled to be 15-45%.

5. The method according to claim 1, characterized in that In step S2, the auxiliary material includes pyrite powder; Preferably, the pyrite powder is crushed to a mesh size of ≤100 mesh; Preferably, the mass ratio of the pyrite powder to the carrier main material is 1-3:10; Preferably, 0.5-1% by mass of hydroxyethyl cellulose is added to the pyrite powder; Preferably, the auxiliary materials further include active titanium dioxide and / or glass fiber.

6. The method according to claim 1 or 5, characterized in that: In step S2, the aging, air-drying, drying and first calcination process includes: aging at 45-60°C for 24-96h under the condition of controlling the relative humidity at 85-95%, drying at 105-120°C for 3-8h, and calcining at 450-520°C for 1-6h.

7. The method according to claim 4, characterized in that In step S3, the liquid obtained after the solid-liquid separation is diluted with deionized water until the mass fraction of the iron element is 8-15%; and / or, using a pH regulator to adjust the pH value of the liquid obtained after the solid-liquid separation to 1-2.5; Preferably, the pH adjuster comprises one or more of ammonium carbonate, ammonia water or liquid ammonia.

8. The method according to claim 1, characterized in that In step S3, the temperature of the soaking liquid is controlled to be 55-70° C. during the soaking; And / or, the drying and secondary calcination process includes: drying at 105-150° C. for 3-8 hours, and calcining at 450-520° C. for 1-6 hours.

9. The method according to claim 1, characterized in that: In step S4, the activation includes a first activation and a second activation; Preferably, the first activation is activation at 150-180° C. for 12-24 h; Preferably, the second activation is activation at 420-460° C. for 2-6 h.

10. The method according to claim 9, characterized in that In step S4, the first activated atmosphere includes the tail gas of the first calcination and / or the tail gas of the second calcination; And / or, the second activation atmosphere includes air or a mixed atmosphere containing air.

Citation Information

Patent Citations

  • A high-loading, low-temperature iron-based denitration catalyst and its preparation method

    CN114471564B